The Position and Authority of the Ombudsman in the Government Administration Supervision System: Synergy and Tension with the Authority of the PTUN - Mutiara Jihan Aziza; Dewi Sulastri (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to analyze the position and authority of the Ombudsman in the government administration supervision system and examine its functional relationship with the State Administrative Court, especially in the context of synergy and tension of authority. This research uses normative juridical methods with a legislative, conceptual, and case approach. The data used is in the form of primary, secondary, and tertiary legal materials that are analyzed qualitatively through descriptive-analytical methods with deductive reasoning. The research results show that the Ombudsman and the State Administrative Court have different but complementary authority characters, where the Ombudsman acts as a preventive and corrective non-judicial supervisor, while the State Administrative Court acts as a repressive judicial institution and provides legal certainty. On the one hand, there is a potential for synergy between the two in strengthening the administrative supervision system through a tiered and mutually supportive dispute resolution mechanism. But on the other hand, there is tension in authority caused by paradigm differences, legal force, and the absence of a clear coordination mechanism, which implies legal uncertainty and the effectiveness of supervision. Therefore, it is necessary to strengthen institutional regulation and coordination to optimize the relationship between the two institutions in realizing an accountable and fair government.